Association Between Medication Literacy and Medication Adherence Among Patients With Hypertension - Shi, Shuangjiao; Shen, Zhiying; Duan, Yinglong; Ding, Siqing; Zhong, Zhuqing (Frontiers in Pharmacology, 2019)
Abstract Background: Few studies investigated the association between the medication literacy and medication adherence, as well as the influence of medication literacy on medication adherence in hypertensive patients. The purpose of this study was to explore the effect of medication literacy on medication compliance in hypertensive patients, and to provide reference for improving medication adherence, controlling blood pressure and promoting disease control in hypertensive patients. Methods: 420 hypertensive patients in Changsha were sampled by stratified cluster sampling. The validated medication literacy evaluation scale for hypertensive patients and self-medication adherence scale were distributed for investigation. Results: The mean scores of medication literacy in patients with hypertension was 24.03±5.13. The mean scores of four dimensions of medication literacy of knowledge, attitudes, skills, and behavior literacy were respectively 6.22±2.22, 5.04±1.16, 4.50±2.21, and 8.27±1.90. The average score of self-medication adherence was 4.82±2.11. Knowledge, attitude, and behavioral literacy of medication literacy were the influencing factors on self-medication adherence in hypertensive patients. Conclusion: The level of medication literacy and self-medication adherence of hypertensive patients need to be improved, and the level of medication literacy in patients with hypertension could affect their self-medication adherence. It was suggested that the level of self-medication adherence could be increased by raising the medication literacy level of hypertensive patients, so safer self-medication and blood pressure control could be achieved.